So near yet so far : the public and hidden worlds of Canada-US relations - Hale, Geoffrey E., 1955-; EBOUND Canada (Vancouver : UBC Press, 2012)
"How do politicians, diplomats, and interest groups negotiate the tangled web of Canada-US relations? So Near Yet So Far provides in-depth look at the multiple dimensions of this complex relationship, especially in the period since 9/11. It bridges the traditional gap between academic perspectives and those of diplomatic, policy, and government relations professionals to explore both the similarities and very significant differences between the two countries political systems and why both matter to anyone trying to understand or influence policy outcomes in both countries.
Based on almost 200 interviews with current and former government policy makers, opinion-shapers, and interest group leaders in both countries, the book analyzes the motives and mechanics of managing cross-border relations at several levels, including political-strategic, trade-commercial, cultural-psychological, and institutional-procedural. A concluding chapter assesses the implications of current policy trends for Canada's foreign and international economic policies.
So Near Yet So Far will be of interest and value to practitioners, scholars, and citizens of both countries who want a better understanding of how the Canada-US relationship works - and can be made to work more effectively. Balanced and fair in its analysis, it gets to the core issues without distorting perspectives on either side of the border."--Pub. desc.
Introduction: The Elephant and the Beaver: Proximity and Distance in Perspective -- Part 1: Three Dimensions of Canada- US Relations -- Guns, Globes, and Gardening: The Political- Strategic Dimension -- Multilevel Games: The Trade- Commercial Dimension -- Neighbo(u)rs, Friends, and Strangers: The Psychological- Cultural Dimension -- Part 2: Tactics and Strategies: Political and Procedural Dimensions -- Governing from the Centre? Political and Policy Coordination in the Management of Canada- US Relations -- Network Diplomacy: Engaging the Executive Branch -- Canada and Congress -- Canadian Public Diplomacy in the United States: Promoting Canadian Interests, Fostering Networks of Influence -- Beyond the Beltway: Federalism, Regionalism, and Cross-Border Relations -- Part 3: Specific Policy Fields -- Smart Borders or Thicker Borders? Homeland Security and Public Safety Policies -- Engaging US Security and Border Policies -- "Just a Trade Dispute"? Proximity and Distance from Different Perspectives -- Shared Energy, Shared Energies? Engaging American Energy Policies -- Conclusion: Managing Bilateral Relations in an Evolving North America.
Includes bibliographical references (pages 384-409) and index.
eBooks on EBSCOhost
Keywords: Canada -- Foreign relations -- 1945-; United States -- Foreign relations -- 2001-2009.; United States -- Foreign relations -- Canada; Canada -- Foreign relations -- United States; Canada -- Relations extérieures -- 1945-; États-Unis -- Relations extérieures -- 2001-2009.; États-Unis -- Relations extérieures -- Canada; Canada -- Relations extérieures -- États-Unis.; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; Diplomatic relations; Canada; United States; Außenpolitik; Kanada; USA; Since 1945